Cognition and norms: toward a developmental account of moral agency in social dilemmas - Meyer, Leandro F. F.; Braga, Marcelo J. (Frontiers in Psychology, 2015)
Most recent developments in the study of social dilemmas give an increasing amount of attention to cognition, belief systems, valuations, and language. However, developments in this field operate almost entirely under epistemological assumptions which only recognize the instrumental form of rationality and deny that “value judgments” or “moral questions” have cognitive content. This standpoint erodes the moral aspect of the choice situation and obstructs acknowledgment of the links connecting cognition, inner growth, and moral reasoning, and the significance of such links in reaching cooperative solutions to many social dilemmas. Concurrently, this standpoint places the role of communication and mutual understanding in promoting cooperation in morally relevant conflicts of action in a rather mysterious situation. This paper draws on Habermas’s critique of instrumental action, and on the most recent developments in institutional and behavioral economics with a view to enhancing our knowledge of the interventions used to cope with social dilemmas. We conclude the paper with a brief presentation of a research strategy for examining the capacity of alternative developmental models to predict dissimilar choices under similar incentive conditions in social dilemmas.